IL-2 based cancer immunotherapies: an evolving paradigm - Rokade, Sushama; Damani, Anita Mehta; Oft, Martin; Emmerich, Jan (Frontiers in Immunology, 2024)
Discovered over 4 decades ago in the supernatants of activated T cells, interleukin-2 (IL-2) is a potent pleiotropic cytokine involved in the regulation of immune responses. It is required for effector T cell expansion and differentiation as well as for peripheral tolerance induced by regulatory T cells. High-dose IL-2 treatment was the first FDA-approved immunotherapy for renal cell carcinoma and melanoma, achieving single agent complete and durable responses, albeit only in a small proportion of patients. The therapeutic potential of wild type IL-2 is clinically limited by its short half-life and severe vascular toxicity. Moreover, the activation of regulatory T cells and the terminal differentiation of effector T cells on IL-2 pose additional restrictions. To overcome the toxicity of IL-2 in order to realize its full potential for patients, several novel engineering strategies are being developed and IL-2 based immunotherapy for cancer has emerged as a burgeoning field of clinical and experimental research. In addition, combination of IL-2 with PD-1/L1 pathway blockade shows vastly improved anti-tumor efficacy over either monotherapy in preclinical tumor models. In this review we discuss the biological characteristics of IL-2 and its receptors, as well as its efficacy and treatment limiting toxicities in cancer patients. We also explore the efforts aimed at developing novel and safer IL-2 therapies to harness the full therapeutic potential of this cytokine.